Mapping of initiatives to increase membership in mutual health organizations in Benin - Turcotte-Trembla; Haddad Slim; Yacoubou Ismaïlou; Fournier Pierre (BMC, 2012)
Abstract Introduction Mutual health organizations (MHO) have been implemented across Africa to increase access to healthcare and improve financial protection. Despite efforts to develop MHOs, low levels of both initial enrolment and membership renewals continue to threaten their financial viability. The purpose of this study was to map initiatives implemented to increase the pool of MHO members in Benin. Methods A multiple case study was conducted to assess MHOs supported by five major promoters in Benin. Three months of fieldwork resulted in 23 semi-structured interviews and two focus groups with MHO promoters, technicians, elected members, and health professionals affiliated with the MHOs. Fifteen non-structured interviews provided additional information and a valuable source of triangulation. Results MHOs have adopted a wide range of initiatives targeting different entry points and involving a variety of stakeholders. Initiatives have included new types of collective health insurance packages and efforts to raise awareness by going door-to-door and organizing health education workshops. Different types of partnerships have been established to strengthen relationships with healthcare professionals and political leaders. However, the selection and implementation of these initiatives have been limited by insufficient financial and human resources. Conclusions The study highlights the importance of prioritizing sustainable strategies to increase MHO membership. No single MHO initiative has been able to resolve the issue of low membership on its own. If combined, existing initiatives could provide a comprehensive and inclusive approach that would target all entry points and include key stakeholders such as household decision-makers, MHO elected members, healthcare professionals, community leaders, governmental authorities, medical advisors, and promoters. There is a need to evaluate empirically the implementation of these interventions. Mechanisms to promote dialogue between MHO stakeholders would be useful to devise innovative strategies, avoid repeating unsuccessful ones, and develop a coordinated plan to promote MHOs.